Caracterização das áreas de preservação permanente urbanas no município de Dois Vizinhos - PR - Hissi, Camila de Castro (2017)
The development process of society is under the occupation of natural areas, and the modification of the physical and biological environment. For urban areas, a major concern is to ensure conservation of permanent preservation areas (APP), regulated by the Forest Code 2012. In Paraná, the limits of urban APP defined in Law No. 18,295 / 2014. The use of geotechnology is a valuable stamp tool for characterizing areas of ecological value and risk, from satellite images. The methodology was based on the use of programs in GIS environment, obtaining MDTs, and using BING 2014 image plus zoning image provided by the city, but not disclosed in the present work, to generate the sources in the urban perimeter and later To verify in locus the existence and condition of these and their streams. Thus, it was possible to identify 11 springs in spite of the GIS environment, of which only 2 were found. The data generated produced an important material to compose the environmental quality management of these sites with regard to the PPAs, and can contribute to the environmental development, having detected the need for monitoring and recovery work in the municipality of Dois Vizinhos-PR.